(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
A new electronic tester consisting of capacitive sensors and optical sensors is now introduced into raw silk inspection. Compared with the traditional seriplane test, the quality indices change a lot. In assessing the yarn evenness, the electronic tester measures the coefficient of variation of the raw silk size (CV_even%, CV_5 m%, CV_50 m%), while the seriplane uses evenness II. In assessing the yarn defects, the electronic tester measures the slubs, thick places and thin places, SIE (small imperfection element), while the seriplane test uses cleanness and neatness. However, raw silk users who have been used to the seriplane test report want to know how to interpret the electronic test indices, they want to be convinced by knowing the correlation between the indices of the two test systems. In this study 50 lots of raw silk are sampled and tested by the two test systems, and the correlation coefficients of the corresponding indices are computed and analyzed. The result shows that there are significant correlation between evenness II and CV_5 m%, a strong correlation between cleanness and slub by the optical sensor, a strong correlation between neatness and SIE by both the capacitive and the optical sensor, and a strong correlation between neatness and the thick and thin places by optical sensor. The result confirms the substitution of the electronic test for seriplane test in future from the technical viewpoint.